The Castrum of Burnum: between old Excavations and new Researches (Archaeologia Adriatica, 2011)
The remains of Roman Burnum are located on the right bank of the river Krka, an area today part of the Krka National Park. The information available about the site is mostly based on the excavation campaigns carried out by the Austrian Archaeological Institute of Vienna between 1912 and 1913, and between 1973 and 1974. In latter years, the Burnum’s acqueduct was investigated also by the Archaeological museum of Zadar. In 2003 archaeologists from the University of Zadar and Municipal Museum of Drniš started to excavate amphitheatre in Burnum. Between 2005 and 2007, Laboratory of Archaeological Survey of the Department of Archaeology of the University of Bologna (Laboratorio di Rilievo delle Strutture Archeologiche del Dipartimento di Archeologia dell’Università di Bologna) conducted three campaigns using non-invasive methods.
Keywords: Burnum; Roman military; Dalmatia; non-invasive archaeological methods